MADRASAH MANAGEMENT IN IMPROVING TEACHER PROFESSIONALITY (SURVEY AT MIN JAMBI CITY) - Suyanto, Suyanto; Abd Rahman; Vivi Yumarni (Dinasti International Journal of Digital Business Management, 2020)
Madrasah management is an activity to empower and coordinate all resources through the planning process, organize, move or implement and supervise to achieve predetermined goals in an effective and efficient manner, including managing teacher professionalism, which can be carried out through education at a higher level according to academic qualifications, Teacher Certification program, Education and Training and training for teachers, Reading Teacher Movement (G2M), KKG organization (Teacher Working Group) and always productive in producing works in the field of education. Characteristics of professional teachers include obeying regulations, maintaining and improving professional organizations, maintaining relationships with peers, guiding students, creating a good atmosphere in the workplace, obeying leaders and love of work.